Reglas de Las Derivadas
Reglas de Las Derivadas
Reglas de Las Derivadas
COMPOSICIÓN
D f g ( x ) = f ' g ( x ) .g ' ( x )
(Regla de la cadena)
(
D f g h ( x ) ) = f ' ( g h ( x ) ) .g ' h ( x ) .h ' ( x )
D ( xk ) = k.x k −1
D f ( x )
k
= k. f ( x ) k −1
. f '( x)
D ( x ) = D(x ) = 21x12
D f ( x) =
1
2 f ( x)
. f '( x)
POTENCIA
1
D = D ( x −1 ) = − 2
1
x 1 1
x D =− . f '( x)
f ( x )
f ( x )
2
−1
FUNCIONES ARCO D ( arccos x ) = −1
(Inversa o recíproca de las 1 − x2 D arccos f ( x ) = . f '( x)
1 − f ( x )
2
trigonométricas) 1
D arctan x =
1 + x2 1
D arctan f ( x ) = . f '( x)
1 + f ( x )
2
D ( ex ) = ex D e ( ) = e ( ) . f ' ( x )
f x f x
D ( a x ) = a x .ln a
EXPONENCIALES
D a ( ) = a ( ) .ln a. f ' ( x )
f x f x
1 1
D ( ln x ) = D ln f ( x ) = . f '( x)
x f ( x)
LOGARÍTMICAS 1 1
D ( log a x ) = . D log a f ( x ) =
1
.
1
. f '( x)
x ln a f ( x ) ln a